"I went in bitterness": Theological implications of a trauma theory reading of Ezekiel. (November 2014) - Garber, David G.
Recent trends in scholarship of the exile, particularly on the book of Ezekiel, have been influenced by refugee and trauma studies. In addition, some evaluations of Ezekiel's theology have decried the book's misogynistic tendencies as well as one of the over-arching theological messages of the prophet: that the community in exile suffered dislocation and the destruction of the temple because of religious infidelity. This article will explore the theological implications of a conversation between Ezekiel scholarship and literary trauma theory. A reading of Ezekiel that focuses on the way the text testifies to trauma (instead of how it explains it) provides room to explore the community's articulation of its experience while acknowledging the possible dangers of its theological conclusions.